Influencia de estilos de apego en conflictos de comunicación de tres parejas en adultez emergente (2016)
The relationships go through many stages and all communication between its members is fundamental to the way they will face the different conflicts which arise. Attachment styles developed in childhood with parents or caregivers have influence on the relationships that a person engages in later periods of the life cycle. This work had as main purpose to establish the influence of attachment styles in communication conflicts of three couples of young lovers. This is a descriptive research with qualitative and crossover design, in which the information was collected through the Structured Attachment Interview George, Kaplan and Main (1996) cited by Casullo and Fernandez (2004) and the Survey on poor communication Lopez (2013), instruments that were applied to three young couples boyfriends, residents in the city of Cali. The results show that attachment style developed in childhood has a direct influence on the way the communication conflicts faced in three pairs. It was evident in one of the women involved style insecure, anxious-ambivalent attachment, which generates feelings of insecurity and anxiety, and fear not manifest lose your partner and return to being abandoned as happened in his childhood. In other young people a safe, same attachment that allows them to seek mutually agreed conflict in their relations through dialogue and empathy solutions is observed.